Cardiac manifestations in Finnish gelsolin amyloidosis patients. (3rd July 2021) - Mustonen, Tuuli; Holkeri, Arttu; Holmström, Miia; Atula, Sari; Pakarinen, Sami; Lehmonen, Lauri; Kiuru-Enari, Sari; Aro, Aapo L.
Abstract: Introduction: Finnish gelsolin amyloidosis (AGel amyloidosis) is an inherited systemic amyloidosis with well-known ophthalmological, neurological and cutaneous symptoms. Additionally, cardiomyopathies, conduction disorders and need of cardiac pacemakers occur in some patients. This study focuses on electrocardiographic (ECG) findings in AGel amyloidosis and their relation to cardiac magnetic resonance (CMR) changes. We also assessed whether ECG abnormalities were associated with pacemaker implantation and mortality. Materials and methods: In this cohort study, 51 genetically verified AGel amyloidosis patients (mean age 66 years) without cardiac pacemakers underwent 12-lead ECG and CMR imaging with contrast agent in 2017. Patients were followed-up for 3 years. Results: Conduction disturbances were found in 22 patients (43%). Nine (18%) presented with first-degree atrioventricular block, six (12%) with left anterior hemiblock, seven (14%) with left or right bundle branch block and two (4%) with non-specific intraventricular conduction delay. Low QRS voltage was present in two (4%) patients. Late gadolinium enhancement (LGE) concentrating on the interventricular septum and inferior parts of the heart was present in 19 (86%) patients with conduction abnormalities. During the follow-up, only one patient received a pacemaker, and one patient died. Discussion: Conduction disorders and septal LGE are common in AGel amyloidosis, whereas other ECG and CMR findings typically observed in most common cardiac amyloidosis types were rare. Septal pathology seen in CMR may interfere with the cardiac conduction system in AGel amyloidosis, explaining conduction disorders, although pacemaker therapy is rarely required.